Effect of Enterprise Risk Management on Company Value with Profitability and Capital Structure as Moderation Variables in LQ45 Companies (period 2020-2023): English - sharfina, sharfina; Deannes Isynuwardhana (LP2M IAIN Palopo, 2025)
This study aims to analyze the effect of implementing Enterprise Risk Management (ERM) based on the COSO framework on firm value, considering profitability and capital structure as moderating variables. Firm value is an important indicator in reflecting the performance and prospects of an entity, especially in the context of companies included in the LQ45 index on the Indonesia Stock Exchange. This study uses a quantitative approach with secondary data obtained from annual reports and stock market information of LQ45 companies during the 2020–2023 period. The analysis method used is moderated regression to test the relationship between ERM and firm value, as well as the moderating role of profitability (measured by Return on Assets) and capital structure (measured by Debt to Equity Ratio). The results of the study indicate that ERM has a positive effect on firm value. In addition, profitability and capital structure are proven to strengthen the relationship. These findings emphasize the importance of integrated risk management and strengthening internal financial performance to increase firm value amidst maximum market dynamics.